Analisis Pandangan Idealisme Plato tentang Konsep Pendidikan - Enjang, Enjang; Supandi, Didi (Addabani: Interdisciplinary Journal of Islamic Education, 2024)
In his theory of idealism, Plato emphasized that to achieve perfection, every student must take a tiered education from childhood to tertiary level. For this reason, through this research, the researcher aims to reveal Plato’s idealistic theory regarding the concept of education. Researchers use a qualitative descriptive approach and content analysis methods to find meaning, measure and correspond to each word and concept in the text. Researchers also attempt to describe and analyze Plato’s ideas of idealism in education. The results of this research then gave rise to the concept of position, process, goals/achievements, and stages of learning based on Plato’s ideological perspective. Henceforth, it is hoped that it will be able to contribute significantly to the world of education.